The Analysis of Motivation Towards Luxury Car Consumption in Surabaya - Samuel Sutanto (iBuss Management, 2015)
Indonesia has a big potential in automotive sales and automotive business. The number of car consumed by public is proven increased in drastic every year, as followed by the consumption of luxury car in Indonesia. According to the data, Mercedes Benz considered as the best automotive brand that provide and sold luxury car in Indonesia. This thing is very interesting to be analyzed considered the price offered is quite high for the luxury car and the competition is very stiff in Indonesia. This research conducted to analyze the motivation of consumer behind the luxury car consumption in Surabaya using the simple random sampling. The data obtained by spreading questionnaires to 100 respondents in Surabaya, then analyzed using Multiple Linear Regression Analysis. The result showed that motivation proven to have significant effect towards the luxury car consumption in Surabaya. Personal value and personal motivation as part of the motivation is proven to have big effect toward luxury car consumption in Surabaya Keywords: Motivation, consumption, automotive, consumer behavior